Cetaceans of the oceanic northern Gulf of Mexico: Distributions, group sizes and interspecific associations - Maze-Foley , K.; Mullin, K. D. (J. Cetacean Res. Manage., 2023)
The Gulf of Mexico is a subtropical ocean basin with a diverse oceanic cetacean community. Cetacean research in the Gulf of Mexico has been driven by mandates of the US Marine Mammal Protection Act as well as concerns over the rapidly expanding oil and natural gas industry and related potential threats (e.g. seismic surveys, increased ship traffic, oil spills). Previously, cetacean distribution and abundances for specific Gulf of Mexico areas or species have been described based on work over periods of several years, and recently abundance estimates were made for the entire oceanic northern Gulf of Mexico (1996-2001). For each cetacean species, the paper describes distribution, group size, associated sea surface temperature and water depth and interspecific associations based on surveys conducted over 11 years that span the entire northern Gulf of Mexico. This dataset is the most comprehensive to date for the oceanic northern Gulf. Nine ship surveys totalling 45,462km of effort were conducted during spring seasons (1991-2001) in continental shelf-edge and oceanic waters ( 100m) of the northern Gulf of Mexico. Eighteen species were identified from 1,868 sightings. Cetaceans were found throughout the area although some species had localised distributions or occurred in restricted ranges of water depths. Spinner dolphins (Stenella longirostris) had the largest mean group size (n = 40, x – = 151.5, SE = 30.90), followed by melon-headed whales (Peponocephala electra), clymene dolphins (S. clymene), pantropical spotted dolphins (S. attenuata), Fraser’s dolphins (Lagenodelphis hosei) and striped dolphins (S. coeruleoalba) (range of means 46.1-99.6). Beaked whales (Ziphiidae), Bryde’s whales (Balaenoptera edeni/brydei), sperm whales (Physeter macrocephalus) and pygmy/dwarf sperm whales (Kogia spp.) were found in the smallest groups (x – < 3). Twenty-seven sightings (1.4% of all sightings) were composed of two cetacean species. Common bottlenose dolphins (Tursiops truncatus) were recorded in mixedspecies groups with more species than any other cetacean. Forty-five cetacean sightings (2.4% of all sightings) were associated with at least one bird species, and 21 (1.1% of all sightings) were associated with schools of fish. Contrary to previous reports, pantropical spotted dolphins were observed in association with both fish (including surface tunas) and seabirds, although to a lesser extent than for other tropical oceans. No mixed pantropical spotted and spinner dolphin groups were sighted despite their regular co-occurrence in other tropical oceans.